High performance computing : 32nd International Conference, ISC High Performance 2017, Frankfurt, Germany, June 18-22, 2017, proceedings /: 32nd International Conference, ISC High Performance 2017, Frankfurt, Germany, June 18-22, 2017, proceedings. (2017) - Unknown
No abstract available